2017
DOI: 10.1038/s41598-017-03896-2
|View full text |Cite
|
Sign up to set email alerts
|

Long days enhance recognition memory and increase insulin-like growth factor 2 in the hippocampus

Abstract: Light improves cognitive function in humans; however, the neurobiological mechanisms underlying positive effects of light remain unclear. One obstacle is that most rodent models have employed lighting conditions that cause cognitive deficits rather than improvements. Here we have developed a mouse model where light improves cognitive function, which provides insight into mechanisms underlying positive effects of light. To increase light exposure without eliminating daily rhythms, we exposed mice to either a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 60 publications
(77 reference statements)
1
11
1
Order By: Relevance
“…To restrict our analyses to the ZT14-15 time point during jet lag, we analyzed short-term memory with the object placement and novel object recognition tests. In a study that was not as ZT restricted as our study, testing memory at 2 h or 24 h after the initial pretest demonstrated that a 20:4 LD cycle positively affected memory performance when compared with 12:12 LD (Dellapolla et al, 2017). Although we did not observe a difference in memory in our pre–jet lag analyses, this study supports our findings during jet lag that the least severe disruption to memory was observed in 16:8 LD compared with 8:16 LD.…”
Section: Discussioncontrasting
confidence: 44%
“…To restrict our analyses to the ZT14-15 time point during jet lag, we analyzed short-term memory with the object placement and novel object recognition tests. In a study that was not as ZT restricted as our study, testing memory at 2 h or 24 h after the initial pretest demonstrated that a 20:4 LD cycle positively affected memory performance when compared with 12:12 LD (Dellapolla et al, 2017). Although we did not observe a difference in memory in our pre–jet lag analyses, this study supports our findings during jet lag that the least severe disruption to memory was observed in 16:8 LD compared with 8:16 LD.…”
Section: Discussioncontrasting
confidence: 44%
“…Importantly, we can conclude that the pond snail's ability to learn, consolidate, and maintain memory may be impaired in habitats where they are exposed to a bright artificial nightlight. This finding is consistent with previous reports suggesting that photoperiod influences circadian activity, learning, and memory in mammals (Dellapolla et al 2017;LeGates et al 2012;Loh et al 2010;Ma et al 2007;MacDonald et al 2007;Smarr et al 2014). Moreover, a recent study using Drosophila melanogaster also has emphasized that disrupting its light-dark cycle effect LTM (Inami et al 2020).…”
Section: Discussionsupporting
confidence: 93%
“…In contrast to other studies in which light produces cognitive deficits in nocturnal rodents, Dellapolla et al [ 116 ] found that long photoperiod enhances long-term recognition memory in mice, measured by spatial object recognition and novel object recognition tasks. Interestingly, whereas clock genes in the hippocampus were rhythmic in a neutral 12 hr photoperiod, rhythms of Per1 , Per2 , Cry1 , and Cry2 were reduced in long days.…”
Section: Photoperiod-induced Plasticity In Other Brain Regionsmentioning
confidence: 74%